Validity and Reliability Content of Physics Problem Solving Test Instrument Based on Local Wisdom - Octafia, Dwiana; Supriyadi, Supriyadi; Sulhadi, Sulhadi (Journal of Research and Educational Research Evaluation, 2020)
This research was part of the research development a instrument test for the ability to solve physics problems based on problems that occur in the field, that is an instrument for assessing the ability to solve problems that has not been tested. The purpose of this study was to reveal the validity and reliability of the contents of the physics problem solving ability test instrument that had previously been compiled. The research method used is a quantitative description by 5 expert judgments. The instrument developed in the form of an expert observation sheet with 3 aspects of assessment, namely aspects of content feasibility, aspects of construction and aspects of language. Analysis of the content validity of the observation sheet using the V coefficient by Aiken and the reliability of the instrument content using the Inter-class Correlation Coefficient (ICC) analysis with the help of SPSS version 16.0. Based on the results of the study, it shows valid results with all item items valued> 0.3, those are with the lowest index 0.6 and the highest 1.0. Inter-rater reliability test using ICC obtained a value of 0.630, which means that all aspects of the instrument for assessing the ability of physics problem solving that have been assessed have a level of consistency. Based on the results of these studies, the test instrument for the ability to solve physics problems is feasible to use.